2009
DOI: 10.1007/s00415-009-5223-2
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II alleles in patients with multiple sclerosis in the Biscay province (Basque Country, Spain)

Abstract: Genetic susceptibility to multiple sclerosis (MS) is associated with genes of the major histocompatibility complex, particularly with the HLA DRB1*1501-DQA1*0102-DQB1*0602 haplotype in Caucasians. To investigate the association of DRB1, DQA1 and DQB1 alleles and haplotypes with MS in Biscay, Basque Country, northern Spain, we examined 197 patients and 200 regionally matched controls. High resolution HLA class II typing was performed by polymerase chain reaction followed by sequence-specific oligonucleotide pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 82 publications
2
27
1
Order By: Relevance
“…As it is shown in Table 4 the maximum and minimum allelic frequencies in patients have been found in Sweden and Mexico respectively until now [18,27]; thus the greatest association and the smallest p value have been observed in Sweden [18]. The frequency of HLA-DRB1*1501 allele was 41.5% in our population that is almost similar to that of Spain with allelic frequency of 45.9% in MS population and nearly in line with the study was conducted by Ghabaee et al which frequency of the allele 46% was reported [5,15].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As it is shown in Table 4 the maximum and minimum allelic frequencies in patients have been found in Sweden and Mexico respectively until now [18,27]; thus the greatest association and the smallest p value have been observed in Sweden [18]. The frequency of HLA-DRB1*1501 allele was 41.5% in our population that is almost similar to that of Spain with allelic frequency of 45.9% in MS population and nearly in line with the study was conducted by Ghabaee et al which frequency of the allele 46% was reported [5,15].…”
Section: Discussionsupporting
confidence: 89%
“…The recruited patients originated from south west of Iran. Our results are in line with most of the other previous studies in different ethnic groups in Iran [5][6][7]9] and European populations [12][13][14][15]25]. So we can conclude that HLA-DRB1*1501 can be considered as a strong genetic risk factor for MS in our population.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…There is also a robust literature showing that certain class II HLA types occur less frequently in MS patients than that in healthy individuals: these include HLA-DR1, HLA-DR4, HLA-DR6, HLA-DR7, HLA-DR9, HLA-DR11 and HLA-DR14 types (Balnyte et al 2012;Barcellos et al 2006;Cocco et al 2012Cocco et al , 2013DeLuca et al 2007;Dyment et al 2005;Fernandez et al 2009;Greer and Pender 2005;Kaimen-Maciel et al 2009;Link et al 2012;Masterman et al 2000;McDonnell et al 1999;Qiu et al 2011a;Stankovich et al 2009;Wu et al 2010a;Zhang et al 2011). It should be noted, however, that many of the studies from which this information is derived only reported HLA typing at the serotyping or two digit level and that some of these "protective" HLA types consist of many different alleles with markedly different amino acid sequences in regions forming the antigen-binding grooves of the HLA molecules, as discussed further below.…”
Section: Hla Moleculesmentioning
confidence: 98%
“…northern European countries 5 ; DRB1*15:01, DRB1*03:01 and DRB1*04:05 in Italy (Sardinia Islands) 6 ; DRB1*15:01-DQA1 *01:02-DQB1*06:02, DRB1* 04:02-DQA1*03:01-DQB1*03:02 and DRB1*13:03-DQA1*05-DQB1*03:01 in Spain (in the province of Biscay) 7 ; DRB1*15:01 and DQB1*0:602 in Ireland 8 ; and DRB1*04:03 and DRB1*08:02 in Mexico 9 . An association was also found between MS and the DQA1*01:02 and DQB1*06:02 haplotypes in African-Brazilian patients whether the DRB1*15:01 allele was absent 10 .…”
mentioning
confidence: 99%